Risk factors for carbapenem-resistant Pseudomonas aeruginosa infection in a tertiary care hospital in Serbia - Zorana Djordjevic; Marko Folic; Dejana Ruzic Zecevic; Goran Ilic; Slobodan Jankovic (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the full text